Identification of Trichoderma spp. from West Iran - J. AMINI and J. ABDOLLAHZADEH, M. ROUGHANIAN, D. ZAFARI*, (Indian Phytopathology, 2013)
In this study sampling was performed from different hosts in Kurdistan province, Iran. Morphology of more than 430 Trichoderma isolates was studied base on the characteristics and classified into two sections including Pachybasium and Trichoderma; 143 isolates belonging to Pachybasium section and 287 isolates belonging to Trichoderma section. For identification of the isolates different morphological characteristics such as colony radius in different media and under various temperatures, morphology and size of conidium, conidiophore, phialide, chlamydospore and mycelia were studied. T. brevicompactum and T. virens from Pachybasium section, T. harzianum from Trichoderma section. The results showed that most frequently encountered species were T. harzianum and T. virens, respectively. These species have been isolated from various parts of the plants and reported for the first time and T. harzianum has been isolated as endophyte from the roots of Nicotiana tabacum.